Artificial neural networks (ANNs) in food science a review - Goyal, Sumit (International Journal of Scientific World, 2013)
Artificial Neural Networks (ANNs) have been applied in several areas,Â viz., science and technology, engineering, agriculture, life sciences and medicine as they have a remarkable ability to provide accurate results. This communication highlights the systematic information available in the literature concerning the implementation of ANN models for predicting properties of dairy products, fruits, vegetables and meat. The information presented in this review paper shows that over the last decade research related to ANN based predictive modelling in food science has picked up.